Vocal cord abnormal voice flow field study by modeling a bionic vocal system. (2nd January 2020) - Zhang, Xiaojun; Wang, Yan; Zhao, Wei; Wei, Wei; Tao, Zhi; Zhao, Heming
ABSTRACT: Vocal cord diseases can cause irregular vibration of the vocal cords, resulting in abnormalities. Therefore, it is necessary to study abnormal vocal cords in a vocal cord model. Research that focuses on vocal cord diseases mainly combines acoustic parameters and pattern recognition. However, it is also important to study the causes of vocal abnormalities in vocal cord diseases. In this paper, a bionic vocal system is modeled, and the influence of pulmonary airflow changes on glottic vibration excitation is analyzed. The effects of asymmetric vocal polyps on changes to the vocal airflow and flow field are studied, showing that the proposed model can assist in the detection of abnormal voice. GRAPHICAL ABSTRACT: